Ambient moisture causes methomyl residues on corn plants to rapidly lose toxicity to the pest slug, Arion subfuscus, Müller (Gastropoda, Stylommatophora). (September 2021) - Nottingham, Louis B.; Kuhar, Thomas P.
Abstract: The carbamate insecticide methomyl is sometimes used to control slugs in field corn and soybean by foliar applications, but control outcomes in research trials and commercial operations have been mixed. In this study, laboratory bioassays were conducted on dusky slug, Arion subfuscus Müller, a common pest of corn and soybean in the Mid-Atlantic United States, to evaluate residual toxicity of Lannate LV (methomyl) at low and high concentrations corresponding to label recommended field rates, and if toxicity may be affected by ambient moisture or repellency to treated plants. Without wetting events, methomyl residues on corn plants caused 90–100% mortality of A. subfuscus for two days and 70–90% mortality for six days. When corn plants were briefly misted with ca. 0.3 cm of water 6 h after methomyl application, mortality was 36% 12 h after treatment, and 0 to 5% 24 h after treatment for both low and high rates. Repellency of A. subfuscus to corn plants treated with the high rate of methomyl was narrowly significant ( P = 0.04) and low rate was not significant. These results suggest that high ambient moisture needed to elicit slug activity in the field also abates toxicity of methomyl residues, explaining why field control is usually poor despite high mortality in the lab. Graphical abstract: Image 1 Highlights: Experiments examined why methomyl residues are toxic to slugs in the lab and not in the field. Methomyl residues were toxic to A. subfuscus slugs for six or more days under dry lab conditions. A brief misting of water over methomyl-treated corn plants triggered rapid detoxification. Minor repellency of A. subfuscus to methomyl residues was also detected. Slugs only emerge during moist weather conditions in the field, so a lethal dose from methomyl residues is unlikely.